Analisis Peran Keuangan Syariah dalam Pembangunan Ekonomi - Yuliyanti, Nanda Putri; Wijaya, Taufiq (JES (Jurnal Ekonomi Syariah), 2024)
The role of Shariah finance in economic development has been the subject of increasing research and policy discourse. Although empirical evidence of the sharia financial impact remains varied and contextual, sharia finance has the potential to make a positive contribution to economic growth, financial stability, and social well-being. Nevertheless, there are still significant challenges and complexities in realizing the Sharia financial potential as a catalyst for economic development. The study aims to explain the multi-faceted contribution of Islamic finance to economic development. In this research the method used is qualitative method. A systematic review of literature is carried out to build a theoretical foundation, conceptual framework, and empirical evidence related to the role of Shariah finance in economic development. The review includes scientific articles, books, reports, and policy documents from a variety of disciplinary perspectives, including economics, finance, Islamic studies, and development studies. The results of this study conclude that Islamic finance plays a role in promoting financial inclusion, encouraging investment in sustainable infrastructure and business, enhancing stability through risk-sharing mechanisms, and promoting ethical and socially responsible financial practices. By providing financial products and services in line with Sharia principles, Sharia financial institutions can meet the unique financial needs of various segments of society, thereby helping to reduce gaps in access to finance and enhance economic empowerment